(у+3)/(2у+2) - (у+1)/(2у-2) + 3/(у²-1) =
= (у+3)/2(у+1) - (у+1)/2(у-1) + 3/(у-1)(у+1) =
= (домножим 1 дробь на (у-1), 2 - на (у+1), 3 - на 2 и получим) =
= (у+3)(у-1)/2(у+1)(у-1) - (у+1)(у+1)/2(у-1)(у+1) + 2*3/2(у-1)(у+1) =
= ( (у+3)(у-1) - (у+1)(у+1) + 2*3) / 2(у-1)(у+1) =
= (у²-у+3у-3 - у²-2у-1 + 6) / 2(у-1)(у+1) =
= 2 / 2(у-1)(у+1) = 1 / (у-1)(у+1) = 1/(у²-1)
1) 1+1= 2- на 7 остановке
2) 2+2= 4- на 6 остановке
3) 4+4= 8 - на 5 остановке
4)8+8 = 16- на 4 остановке
5)16+16= 32- на 3 остановке
6)32+32= 64 - на второй остановке
7) 64+64= 128 -было изначально
Ответ: 128
1)182+18=200(д)-он привёз во вторник
2)200:4=50(д)-он привёз в среду
3)182+200+50=432(д)
(х+3)/7=(2х-1)/5
5(х+3)=7(2х-1)
5х+15=14х-7
5х-7х= -7-15
-2х= - 22
х=11